Introducing co-composting to fecal sludge treatment plants in Benin and Burkina Faso: a logistical and financial assessment - Nikiema, Josiane; Tanoh-Nguessan, R.; Abiola, F.; Cofie, Olufunke O. (International Water Management Institute, 2020)
Based on primary data from fecal sludge (FS) treatment plants in three West African urban regions (Ouagadougou in Burkina Faso, Greater Accra in Ghana, and Grand Nokoué in Benin), FS collection and treatment patterns were analyzed to identify possible scenarios for resource recovery (RR) through FS co-composting. FS collection was analyzed for up to 7 years, in part per day, month and season, as well as FS characteristics to understand peak flows, FS qualities and related variations to plan for appropriate RR technology and capacities.